Analisis Kepuasan Mahasiswa Terhadap Kinerja Mengajar Dosen UINSU - Rizki Hambali Hsb; Fajran Rahman Berutu; Dini Lestari (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study intends to evaluate the effectiveness of lecturers in the Management study program at the Faculty of Islamic Economics and Business, UIN North Sumatra, both in terms of student satisfaction and teaching performance. In semester 6 of the management department, which included 108 participants, non-probability sampling using a purposive random sampling approach was used as the sampling strategy. way to collect data through a questionnaire. used descriptive statistical analysis to analyze the data. The results showed that respondents' expectations of the average lecturer teaching performance were in the high category and the level of student satisfaction with lecturer teaching performance was in the satisfied category, while the average lecturer performance was in the good category. It is anticipated that teachers will adhere to a strict work ethic.